Antibacterial and hemostatic capacities of cellulose nanocrystalline-reinforced poly(vinyl alcohol) electrospun mats doped with Tiger 17 and pexiganan peptides for prospective wound healing applications - Teixeira, Marta Albertina (2022)
Infection is a major issue in chronic wound care. Different dressings have been developed to prevent microbial propagation, but an effective, all-in-one (cytocompatible, antimicrobial and promoter of healing) solution is still to be uncovered. In this research, polyvinyl alcohol (PVA) nanofibrous mats reinforced with cellulose nanocrystal (CNC), at 10 and 20% v/v ratios, were produced by electrospinning, crosslinked with glutaraldehyde vapor and doped with specialized peptides. Crosslinking increased the mats' fiber diameters but maintained their bead-free morphology. Miscibility between polymers was confirmed by Fourier-transform infrared spectroscopy and thermal evaluations. Despite the incorporation of CNC having reduced the mats' mechanical performance, it improved the mats' surface energy and its structural stability over time. Pexiganan with an extra cysteine group was functionalized onto the mats via hydroxyl- polyethylene glycol 2-maleimide, while Tiger 17 was physisorbed to preserve its cyclic conformation. Antimicrobial assessments demonstrated the peptide-doped mat's effectiveness against Staphylococcus aureus and Pseudomonas aeruginosa; pexiganan contributed mostly for such outcome. Tiger 17 showed excellent capacity in accelerating clotting. Cytocompatibility evaluations attested to these mats' safety. C90/10 PVA/CNC mats were deemed the most effective from the tested group and, thus, a potentially effective option for chronic wound treatments.